INTRACELLULAR DELIVERY OF CRISPR-CAS9 VIA A SYNTHESIZED LIPID-LIKE NANOPARTICLE LIBRARY FOR GENE EDITING - Bolinger, Justin. (2018)
Abstract: The field of protein therapeutics is an emerging one. One of the evident challenges of protein therapeutics is the method of delivering these proteins, which are often fragile or prone to break down. Lipid nanoparticles (LNPs) represent a class of drug delivery system that has shown promise for providing an efficient vehicle for protein therapeutics. The hypothesis of this study was that fabricated LNPs could carry out CRISPR deliveries of model proteins at transfection efficiencies comparable to a commercially available lipid. 20 LNPs were synthesized using a self-assembly fabrication method to create a congener library. The LNPs comprising this library were confirmed structurally and their physical stability profiles were determined. GFP-Cre was delivered to HeLa-DsRed cells via these LNPs to determine their ability to enable protein uptake by assessing induced GFP fluorescence. Similarly, Cas9:sgRNA complexes targeting GFP were delivered to GFP-HEK cells to assess their GFP knockout efficiencies by assessing GFP fluorescence. 20 formulated and 20 non-formulated LNPs were produced. Transmission electron microscopy and dynamic light scattering analysis were used to confirm that the fabricated LNPs had uniform size and shape as well as uniform stability profiles and relatively homogenous particle size. For the delivery of GFP-Cre with the 20 formulated LNPs, 12 were able to induce GFP fluorescence at a rate of greater than 30%, with 10 performing similar to or better than the positive control, Lipofectamine 2000 (~45% GFP-positive). For the delivery of Cas9:sgRNA with the 20 formulated LNPs, 13 were able to induce GFP knockout at a rate of greater than 30%, with 6 performing similar to or better than the positive control (~65%). MTT assay data showed 6 formulated LNPs which yielded high values for cell viability (greater than 90%). A combination of these data gave us 5 formulated LNPs with high transfection efficiencies and low cytotoxicities, making these LNPs attractive for further research.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Qiaobing Xu.; Committee: Sergio Fantini, and James Van Deventer.; Keyword: Biomedical engineering.